Fundamental Problems of Water Resources Management in the Helmand River Basin, Afghanistan - Salman Ali Nabavi (Randwick International of Social Science Journal, 2024)
The closed hydrology and the geopolitical nature of the Helmand River basin in terms of leadership, management, and use of water resources have created serious threats to its integrity, environmental health, and human security in this river basin. The Helmand River basin, where about 8 million people live, includes about 49 percent of the soil and 11 percent of the water flow of this country. Agricultural sectors and related industries are the main drivers of the economy in this basin and due to the increasing need for food in the country and the region, the population shift towards cities, industrialization, and most importantly climate change and water shortage, competition between major water consumers in this basin is increasing. Despite the increasing number of studies on the water management of the Helmand River basin, no practical research carried out to strengthen and summarize the common conclusions and findings related to the fundamental problems facing the water resources management of this river basin. Therefore, in this article, to fill the aforementioned gap, all related documents, studies, and topics have been comprehensively reviewed and analyzed. To achieve this goal, the qualitative-analytical research method was used to analyze and find the key issues raised, and as a result, the basic problems facing the water resources management of this basin were investigated as much as possible. In the following, the necessary suggestions are also presented so that by implementing it, this country would be able to solve the existing problems by using its hydro political capacities and opportunities and it would also be placed at the center of the water interactions in the river basin, to provide a sustainable and all-round development of the country.